The Nature and Magnitude of the Effects of Asymmetric Regulation of Mobile Termination Rates on the Mexican Retail Prices - Arturo Robles-Rovalo; Emiliano Díaz-Goti; Rodrigo Guarneros-Gutiérrez (International Telecommunications Society (ITS), 2018)
In theory, network profits are independent of the reciprocal termination rates when operators charge nondiscriminatory call prices (Laffont, Rey and Tirole, 1998). Additionally, termination rates can be used to subsidize subscriber acquisition cost. This issue is typically known as a "waterbed effect", where a reduction (increase) in termination rates leads to corresponding increase (reduction) in subscription fees to consumers. We are using a practical case for testing the effects in the final prices for regulatory policy with several changes in mobile termination rates based on an asymmetric price access regulation. In our example, the termination rates have been part of a vertical restriction strategy. The observed network-base price discrimination implemented by the major network (Telcel) resulted in deadweight efficiencies lost and created barriers to new entrance and blocked growth for the small networks OECD (2012). Historically, profits margins and mobile prices comes down whenever regulator have reduced termination rates; following the income effects in subscription (Tangeras, 2014). Having in mind this fact, regulators would diminish termination rates in order to pushdown mobile prices and stimulate competition, rest on a cost-based asymmetric price regulation. The further research allows a statistical assessment of the asymmetric price regulation implemented by the Mexican regulatory authority during January 2013 to June 2017. This paper evaluates if asymmetric regulation brings a better impact in the Mexican consumer welfare, driving the retail prices of mobile services down, also the effectivity of this policy for the next years, taking in to account that there is not significant change in the market share among all mobile networks.
Keywords: L38; L51; L59; L96; O54; 330; Mexico; Mobile Telecommunications; Termination Rates; Structural Change; Asymmetric Regulation; Convergence; Time Series Analysis